Arabinoxylan profiles in Chinese winter wheat: Novel QTL and molecular marker - Tiantian Chen; Xue Gong; Lei Zhi; Hongyu Zhang; Shuanghe Cao; Dan Liu; Cong Zhao; Yan Zhang; Jingdong Liu; He Zhonghu; Yongjing Ni; Yong Zhang; et al. (Elsevier, 2024)
Arabinoxylan (AX) is a significant component of dietary fiber (DF) present in both whole meal and refined flour of wheat. Identifying genetic loci associated with AX content and developing molecular markers can facilitate the breeding of wheat cultivars with increased AX levels through marker-assisted selection (MAS). In our study, we analyzed the AX profiles of 262 recombinant inbred lines (RIL) derived from Zhongmai 578/Jimai 22, along with a natural population consisting of 161 representative wheat varieties in China. Our investigation revealed that Taishan 1 and Shan 715 exhibit WE-AX content comparable to or even superior to Yumai 34, a current benchmark cultivar for high WE-AX content. Additionally, we discovered a novel quantitative trait locus (QTL) in the RIL population, explaining 6.9–19.6% of the phenotypic variance of water-extractable AX (WE-AX) and 7.3–10.2% of the phenotypic variance of total AX (TOT-AX). Notably, a high-throughput competitive allele-specific PCR (KASP) marker was developed and validated in the natural population, expanding our understanding of germplasm with high AX content and providing molecular markers that can be utilized in marker-assisted selection for high AX wheat.